S103 Anti-Pseudomonal Bacteriophage Cocktail Reduces Inflammatory Responses in the Murine Lung. (19th November 2012) - Pabary, R; Singh, C; Morales, S; Bush, A; Alshafi, K; Bilton, D; Alton, EWFW; Smithyman, A; Davies, JC
Abstract : Bacteriophages are naturally occurring viruses that specifically target and infect bacteria and, unlike antibiotics, are able to multiply at infection sites and adapt to resistant bacteria. We hypothesise that bacteriophage cocktails may be useful against P. aeruginosa (Pa) in cystic fibrosis and tested this in a murine infection model. Two strains of Pa were assessed: a) a clinical strain from an adult CF patient, b) a laboratory strain. Both strains were shown to be sensitive to a novel anti-Pseudomonal bacteriophage cocktail on a standard plaque assay. Adult BALB/c mice were inoculated intranasally with 50ul of Pa followed by 20ul of bacteriophage cocktail (treated, n=21) or SM buffer (control, n=21). Twelve mice were sacrificed at 24hrs after infection and the others at 48hr. Bronchoalveolar lavage was serially log diluted, cultured at 37 o C and the remainder centrifuged and supernatant stored at –80 o C for future analysis of soluble inflammatory markers. Total cell counts were determined using a haemocytometer. Non-quantitative splenic cultures were performed. Results: All mice treated with bacteriophage (n=6) had cleared infection at 24hrs compared with none of the controls (n=6) (median [range] CFU/ml 0 [0–0] vs. 1305 [190–4700], p<0.01); inflammatory cell counts did not differ. At the 48hr time point most mice had cleared the infection, with no phage-related differences. However, treated mice demonstrated significantly fewer inflammatory cells in BAL compared with controls (median [range] 4.50 [2.84–5.86] × 104/ml vs. 9.12 [6.93–13.86], p<0.01 for the clinical strain; median [range] 6.04 [5.56–10.60] × 104/ml vs. 9.72 [8.56–15.28], p<0.01 for the laboratory strain). Differential cell counts and measurements of soluble inflammatory mediators are underway. BALB/c mice successfully cle ared this dose of Pa by 48hrs, with an accompanying acute cellular inflammatory response. The reduction in cell number following co-administration of a bacteriophage cocktail to which the organisms were sensitive suggests that Pa was cleared earlier and more effectively in the phage-treated animals; this was confirmed by significant differences in bacterial load at the earlier, 24 hour time point. Further work is underway to explore the therapeutic potential of bacteriophage in pulmonary Pa infection.